Perancangan Prototype Kartu Kontrol Aset TIK untuk Monitoring Inventaris di Diskominfo Kabupaten Nias - Harefa, Johan Berkat; Zebua, Otniel; taviani, lafaurestiok; mendrofa, Ricky; mendrofa, vanessa; gea, elhan (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Information and communication technology (ICT) asset management in various government agencies, including the Nias Regency Communication and Informatics Office, is still largely done manually using physical documents and spreadsheets. This manual process has the potential to cause various problems, such as data loss or damage, duplication of records, input errors, and delays in preparing inventory reports. This condition makes it difficult to track asset status accurately and quickly, resulting in decreased work efficiency. This study aims to design and implement a prototype of a web-based ICT Asset Control Card information system that can be a solution for digitizing the inventory process. This system is expected to facilitate the process of recording, tracking, and reporting assets more effectively, efficiently, and in real-time. The development method used is the Waterfall model consisting of the stages of needs analysis, system design, implementation, testing, and maintenance planning. The system was developed using the CodeIgniter 3 framework, Bootstrap 5, Controller-Model-View (CMV) architecture, and a MySQL database. The testing process was carried out using the black-box testing method to verify system functionality and user acceptance testing (UAT) involving staff from the Nias Regency Communication and Informatics Office as direct users. The research results showed that the system was capable of automating asset recording, tracking, and reporting in real time. The average asset recording time was reduced from 15 minutes to 5 minutes per entry, and 90% of respondents stated that the system was easy to use. This prototype has the potential to be developed into a more secure, flexible, and mobile-compatible integrated inventory system